Immunogenicity and safety of hepatitis B vaccination in patients with type 2 diabetes in China: An open-label randomized controlled trial. Issue 25 (8th June 2021) - Han, Bingfeng; Liu, Wu; Du, Juan; Liu, Hanyu; Zhao, Tianshuo; Yang, Shubo; Wang, Shuai; Zhang, Sihui; Liu, Bei; Liu, Yaqiong; Cui, Fuqiang
Abstract: Objective: Hepatitis B virus (HBV) infection remains a global public health challenge. Patients with diabetes are at greater risk of HBV infection than healthy people. The immunogenicity and safety of two major hepatitis B vaccines were evaluated in Chinese patients with diabetes. Methods: In this phase IV, open-label, randomized, controlled study, participants with diabetes were randomly recruited from 6 township health centers in Gansu Province and received either a 3-dose Saccharomyces cerevisiae recombinant hepatitis B vaccine (Group D20SC 0-1-6, n = 113) or a 3-dose Chinese hamster ovary cell (CHO) recombinant hepatitis B vaccine (Group D20CHO 0-1-6, n = 119). Healthy control groups were randomly recruited from the same 6 health centers and received 3 doses of the saccharomyces cerevisiae recombinant hepatitis B vaccine (Group ND20SC 0-1-6, n = 77). Immunogenicity, including seroconversion rate and geometric mean concentration (GMC) at 1 month after three doses of vaccination, and safety were assessed. The seroconversion rate was defined as the concentration of HBsAb ≥ 10 mIU/mL. Results: The seroconversion rates of Group D20SC 0-1-6, Group D20CHO 0-1-6 and Group ND20SC 0-1-6 were 89.6%, 91.4% and 97.1%, respectively, in the per-protocol analysis, and these differences were not statistically significant. The antibody concentration in Group D20SC 0-1-6 (GMC = 601 mIU/mL) was lower than that of the healthy control group (GMC = 1465 mIU/mL), but no significant difference was found in the GMC between the Group D20CHO 0-1-6 (GMC = 778 mIU/mL) and Group D20SC 0-1-6. Adverse events (AEs) were comparable between groups, and no serious AEs were found in these three groups. Conclusions: The Saccharomyces cerevisiae recombinant and CHO recombinant hepatitis B vaccines in China can induce good immunogenicity in a diabetic population, although the antibody concentration may be lower, indicating the feasibility of vaccinating a large number of diabetic patients in China with these vaccines.